Development of Jiapu Puzzle Interactive Media for Learning Chinese Cultural Kinship System - Anya Linggar Cahyani; Karina Fefi Laksana Sakti; Sri Prameswari Indriwardhani (Nexus Publishing NXP, 2025)
This study aims to develop an interactive learning media called Jiapu Puzzle to support students’ understanding of the kinship system in Chinese culture, which is a crucial component of Mandarin language education. The media was developed using the ADDIE model, which includes analysis, design, development, implementation, and initial evaluation stages. Development involved classroom observations of grade XI IBB students at SMA Laboratorium UM, teacher interviews, and validation by media and content experts. The final product is a family tree puzzle board representing kinship structures on both paternal and maternal sides, complete with narratives and Hanzi illustrations. Validation results showed that the media was highly feasible in terms of visual appeal, content quality, and usability. The implementation stage revealed positive student responses, especially in terms of engagement, enthusiasm, and comprehension. Using a conventional gamification approach, Jiapu Puzzle proved effective as an alternative medium to support engaging and contextual Mandarin language and cultural learning.